Virtual reality eye exercises application based on bates method: a preliminary study - Komang Candra Brata; Hanifah Muslimah Az-Zahra; Adam Hendra Brata; Lutfi Fanani (Institute of Advanced Engineering and Science, 2023)
In many situations, ophthalmologists prescribe glasses and contact lenses as a treatment method for Myopia. The other way to cure myopia is by performing Lasik surgery or using advanced tools which takes a large amount of financial effort. Dr. William Horatio Bates proposed a promising method to cure myopia with an eye exercise approach, providing opportunities to enhance the availability of low-cost eye treatment that is not easily achievable with surgery and other expensive approaches. However, many myopia patients are still unaware of this method and have no idea how to use it in their daily lives. The rapid growth of virtual reality (VR) technology has shown that this technology offers an affordable and effective solution to provide better health services. This paper expands the result of an initial experiment aimed to validate the utilization of mobile VR technology to enhance the possibility of the Bates method implementation as a low-cost daily eye exercise tool. A direct diary study with 14 participants was carried out to explicitly investigate the feasibility of the proposed app. The result reveals that the proposed app could assist people with myopia when doing eye exercises and the result is quite promising in reducing the refractive levels with 0.13 diopter on average within 5 weeks period.